Combinatorial screening using orthotopic patient derived xenograft-expanded early phase cultures of osteosarcoma identify novel therapeutic drug combinations. (1st February 2019) - Loh, Amos H.P.; Stewart, Elizabeth; Bradley, Cori L.; Chen, Xiang; Daryani, Vinay; Stewart, Clinton F.; Calabrese, Christopher; Funk, Amy; Miller, Greg; Karlstrom, Asa; Krafcik, Fred; Goshorn, David R.; et al.
Abstract: Lead discovery in osteosarcoma has been hampered by the lack of new agents, limited representative clinical samples and paucity of accurate preclinical models. We developed orthotopic patient-derived xenografts (PDXs) that recapitulated the molecular, cellular and histologic features of primary tumors, and screened PDX-expanded short-term cultures and commercial cell lines of osteosarcoma against focused drug libraries. Osteosarcoma cells were most sensitive to HDAC, proteasome, and combination PI3K/MEK and PI3K/mTOR inhibitors, and least sensitive to PARP, RAF, ERK and MEK inhibitors. Correspondingly, PI3K signaling pathway genes were up-regulated in metastatic tumors compared to primary tumors. In combinatorial screens, as a class, HDAC inhibitors showed additive effects when combined with standard-of-care agents gemcitabine and doxorubicin. This lead discovery strategy afforded a means to perform high-throughput drug screens of tumor cells that accurately recapitulated those from original human tumors, and identified classes of novel and repurposed drugs with activity against osteosarcoma. Highlights: Few new agents are identified for osteosarcoma due to the paucity of actionable somatic mutations. Patient-derived orthotopic xenografts can expand tumor cells as short term early-phase cultures. High-throughput screens identify novel and repurposed drugs with activity against osteosarcoma. HDAC inhibitors have particular efficacy and are potentiated in combination with anthracyclines.